Islamic Values in The Kupatan Tradition in Banten - Sulton Kholid; Ahmad Ramadhani Chaidir; Amar Mansyur; Ahmad Maftuh Sujana (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Kupatan is a tradition that is still sustainable in various regions in Indonesia, including in Banten. This tradition is carried out after Eid al-Fitr, usually on the seventh day or more, as a form of expression of gratitude and togetherness of the community. This article aims to examine the Islamic values contained in the Kupatan tradition in Banten and its relevance to Islamic teachings. Using descriptive qualitative methods through literature studies and observations, this study found that the Kupatan tradition contains various Islamic values, such as ukhuwah Islamiyah (brotherhood in Islam), gratitude (gratitude to Allah), as well as social concern and almsgiving. In addition, the values of sincerity and cleanliness of heart are also reflected in the Kupatan procession which involves joint prayer and friendship between residents. Thus, the Kupatan tradition in Banten is not only a cultural heritage, but also a manifestation of Islamic teachings that remain relevant in the social life of the Muslim community.